The Effect of Audit Market Competition on Audit Quality in the Iraqi Environment - Nawzad Khudhur Saeed; Dr. Mohammed Huweish Allawi Al-Shujairi; Dr. Vian Sulaiman Hama Saeed (Migration Letters, 2023)
The aim of this study is to measure and analyze the level of competition in the Iraqi auditing market, as well as to evaluate and analyze the quality of auditing for auditing offices and companies operating in the Iraqi environment. The study also seeks to test the relationship between the level of competition and audit quality for these offices and companies. To achieve the study’s objectives, a main hypothesis was adopted to test the relationship between the variables under investigation. The study employed an experimental method based on quantitative evaluation and analysis, utilizing the annual financial data of companies listed in the Iraq Stock Exchange and official market reports as sources of data for the period from 2017 to 2021. The study sample comprised 26 Iraqi auditing offices and companies, selected from a purposive sample of 22 joint-stock companies listed in the Iraq Stock Exchange. The data of these companies were used to evaluate the study variables related to auditing offices and companies in the sample. Taking into account the aforementioned, the study concludes that there is a significant relationship and impact of market competition on the quality of auditing. Additionally, the study finds that the Iraqi auditing market exhibits a strong oligopoly structure and is therefore an inefficient competitive market.